Toward the first documented extinction of a marine macroalga in the Mediterranean Sea? - Emmanuelle Descourvières; Vinko Bandelj; Adriano Sfriso; Martina Orlando-Bonaca; Vesna Mačić; Ljiljana Iveša; Silvija Kipson; Edi Gljušćić; Claudio Battelli; Isabella Moro; Cosimo Solidoro; Annalisa Falace (Regional Environmental Change, 2024)
Fucus virsoides is a glacial relict-species endemic to the Adriatic that was widespread from northern Italy to southern Albania. In recent decades, however, it has suffered an alarming decline. In this study, all available records were reviewed to reconstruct its historical and current occurrence and to investigate the possible causes of its decline. Comprehensive mapping revealed a continuing decline with a significant shift, leaving only about 20 fragmented populations. While the species is already classified as critically endangered in Albania, F. virsoides could be considered functionally extinct in Istria (Croatia), critically threatened with extinction in Italy and Montenegro and locally extinct in Slovenia. The status of the species in the rest of Croatia is still unclear. The remaining populations are located in areas characterised by low temperatures, low salinity and high nutrient concentrations. Long-term analyses of these key abiotic factors revealed profound changes that suggest a link to the species' decline. This study provides a thorough assessment of the overall status of F. virsoides and argues for its inclusion on the IUCN Red List. Immediate conservation measures are needed for the long-term survival of this species.

First report of an aegagropilous form of Cladophora prolifera (Cladophorales, Chlorophyta) from the lagoon of Strunjan (Gulf of Trieste, northern Adriatic) - CLAUDIO BATTELLI; FREDERIK LELIAERT (Mediterranean Marine Science, 2021)
The occurrence of unattached spherical (aegagropilous) populations of the green alga Cladophora prolifera in the marine lagoon of Strunjan (Gulf of Trieste) is reported. Species identification was based on molecular and morphological data, and the distribution, ecology and morphological features of the aegagropilous populations are described. The ball-shaped form of this species differs from the typical upright attached form found on open shores by the radial arrangement of the branches and the absence of cells and rhizoids with clear annular constrictions. The formation of the aegagropilous form of C. prolifera likely results from specific hydrodynamic conditions in the human-mediated environment of the marine lagoon, in combination with morphological development of the species. The Strunjan marine lagoon appears to be the only location in the Mediterranean Sea, or even worldwide, where aegagropilous forms of C. prolifera occur in large abundance. Based on the high associated biodiversity, we propose the inclusion of these populations to be considered in conservation management plans in the area.

The extensive development of the turf-forming red alga Womersleyella setacea (Hollenberg) R. E. Norris (Rhodophyta, Ceramiales) in the Bay of Boka Kotorska, Montenegro (southern Adriatic Sea) - Claudio Battelli; Fabio Rindi (Plant Biosystems, 2008)